2005
DOI: 10.2135/cropsci2005.0163
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size Analysis of Weedy Amaranthus Species

Abstract: is the agricultural land of the Midwest. Given the intense farming practices used and the nearly constant changes Weedy Amaranthus species pose a serious threat to agriculture.in Best Management Practices, agrichemicals used, etc., One of the areas that causes the greatest concern is development of herbicide resistance and subsequent transfer of herbicide resistance the landscape is in a continual state of flux. If interspegenes among the species. To determine the potential impact of inter-cific hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 23 publications
3
52
0
1
Order By: Relevance
“…Grant (1959a) reported that Palmer amaranth chromosomes are small (2 to 3 lm) and not well differentiated. Consistent with this, Rayburn et al (2005) reported the genome size of Palmer amaranth to be smaller than most of the weedy amaranths with 2C ¼ approximately 0.95 pg. Grant (1959a) gave a chromosome count for the species of 2n ¼ 34.…”
supporting
confidence: 61%
“…Grant (1959a) reported that Palmer amaranth chromosomes are small (2 to 3 lm) and not well differentiated. Consistent with this, Rayburn et al (2005) reported the genome size of Palmer amaranth to be smaller than most of the weedy amaranths with 2C ¼ approximately 0.95 pg. Grant (1959a) gave a chromosome count for the species of 2n ¼ 34.…”
supporting
confidence: 61%
“…A major contributor to the noxious nature of these weedy species is their ability to efficiently adapt to the changes in agricultural management practices that are specifically designed to control and prevent colonization. For example, numerous populations of pigweeds have evolved herbicide resistance (Drzewiecki, 2001;Rayburn et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The first reported glyphosateresistant A. palmeri population was 6-to 8-fold more resistant than a susceptible population (3), and the glyphosate resistance mechanism in this population was previously unknown but is not due to differences in absorption or translocation of glyphosate (3). The mechanism is also not due to a ploidy change (3), because glyphosateresistant individuals had the reported A. palmeri genome size (22). Here, we use genetic and molecular analyses of EPSPS genes and proteins from glyphosate-resistant and -susceptible A. palmeri populations and demonstrate that amplification of the EPSPS gene is the glyphosate resistance mechanism.…”
mentioning
confidence: 99%